A Randomized, Double‐Blind Study Comparing Pharmacokinetics and Pharmacodynamics of Proposed Biosimilar ABP 798 With Rituximab Reference Product in Subjects With Moderate to Severe Rheumatoid Arthritis. Issue 8 (5th July 2020) - Burmester, Gerd; Chien, David; Chow, Vincent; Gessner, Melissa; Pan, Jean; Cohen, Stanley
Abstract: ABP 798 is a proposed biosimilar to rituximab reference product (RP), an anti‐CD20 monoclonal antibody. Pharmacokinetics (PK), pharmacodynamics (PD), and safety results from the comparative clinical study that evaluated the PK, PD, safety, efficacy, and immunogenicity of ABP 798 versus rituximab RP are presented here. Subjects with moderate to severe rheumatoid arthritis (RA) received 2 doses of ABP 798, United States‐sourced RP (rituximab US) or European Union‐sourced RP (rituximab EU), each consisting of two 1000‐mg infusions 2 weeks apart. For the second dose (week 24), ABP 798‐ and rituximab EU‐treated subjects received the same treatment; rituximab US‐treated subjects transitioned to ABP 798. End points included area under the serum concentration‐time curve from time 0 extrapolated to infinity and maximum observed serum concentration following the second infusion of the first dose (PK) and percentage of subjects with complete CD19+ cell depletion days 1‐33 (PD). Primary analysis established PK similarity between ABP 798 and rituximab RP based on 90% confidence intervals of the adjusted geometric mean ratios being within a prespecified equivalence margin of 0.8 and 1.25. Complete CD19+ B‐cell depletion on day 3 among groups confirmed PD similarity. These findings demonstrated PK/PD similarity between ABP 798 and rituximab RP in subjects with moderate to severe RA.